2011
DOI: 10.1097/eja.0b013e328346d5a9
|View full text |Cite
|
Sign up to set email alerts
|

The pneumatic tourniquet: mechanical, ischaemia–reperfusion and systemic effects

Abstract: The pneumatic tourniquet is frequently used for upper and lower limb surgery to reduce bleeding, improve visualisation of important structures and expedite surgical procedures. Despite advances in technology, localised tissue damage secondary to cuff compression, ischaemia-reperfusion injuries and systemic complications still occur. The combination of these problems may affect outcome and contribute to prolonged hospitalisation. Use of the correct pneumatic tourniquet cuff size and a patient-specific cuff pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 110 publications
2
118
0
1
Order By: Relevance
“…Nonetheless, Worland et al (1997) showed an important correlation between tourniquet pressure and thigh pain in the immediate postoperative period. Pain relief in the immediate postoperative period following TKA is crucial in facilitating early recovery ( Estebe et al, 2011 ;Worland et al, 1997 ). In our study, there was a signifi cant reduction in postoperative pain in patients using a tourniquet with minimal infl ation pressure.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, Worland et al (1997) showed an important correlation between tourniquet pressure and thigh pain in the immediate postoperative period. Pain relief in the immediate postoperative period following TKA is crucial in facilitating early recovery ( Estebe et al, 2011 ;Worland et al, 1997 ). In our study, there was a signifi cant reduction in postoperative pain in patients using a tourniquet with minimal infl ation pressure.…”
Section: Discussionmentioning
confidence: 94%
“…In previous studies, the deleterious effects of these factors on various cell functions were shown, including mitochondrial oxidative phosphorylation, ATP depletion, activation of protein kinases, phosphatases, proteases, lipases, and nucleases, which might lead to loss of several cellular function and integrity. 24 This cellular dysfunction and disintegrity might play a role in the etiopathology of remote organ damage including liver, kidney and lung in lower limb ischemia-reperfusion injury. [3][4][5]16 The kidneys are particularly involved in the remote alteration phenomenon following skeletal muscle ischemia-reperfusion injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopedic surgery, tourniquets are often used to reduce hemorrhage in the operative field, improve the visualization of important structures, and expedite the surgical procedure [3]. All pneumatic tourniquets including the new generation of automated devices can lead to a wide range of complications, from minor and self-limiting to life-threatening [1].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a tourniquet in orthopedic interventions provides a bloodless surgical site, providing protection against surgical complications and shortening the operation time, and consequently shortening the length of hospital stay [3]. …”
Section: Introductionmentioning
confidence: 99%